Valuing wireless data services solutions for corporate clients using real options. (12th February 2007) - Ramirez, William; Harmantzis, Fotios C.; Tanguturi, Venkata Praveen
The paper deals with wireless data services and their importance in the enterprise world. Provisioning in difficult-to-reach areas of tall buildings is challenging. To extend coverage, operators deploy ad-hoc solutions that are usually costly. Four alternative deployment cases from both the corporate customer's as well as service provider's point of view are proposed and quantified using real options. The objective is to maximise revenue and reduce risk for operators while improve customer satisfaction levels within the budget constraints of the customer. Analysis suggests that savings due to improvements in productivity are much higher than revenues perceived by the service provider.